Climate change perception and its impact on net farm income of smallholder rice farmers in South-West, Nigeria. (10th August 2021) - Ojo, T.O.; Baiyegunhi, L.J.S.
Abstract: Climate change such as extreme weather, unexpected temperature and rainfall fluctuations cause several significant risks to the agro-economy. This study, therefore, assessed the determinants of climate change perception (CCP), the level of perception and its impact on net farm income of rice farmers. This is imperative as the actual CC communication and policy, therefore, require a good understanding of smallholders' views and acknowledgment of individual's perception about CC. Employing cross-sectional data from 360 rice farmers selected from three States in South-West, Nigeria, a Ricardian model was used to analyse climate change impact on rice production. While accounting for selection bias, the study employed a double-hurdle (DH) model to estimate the determinants of farmers' perception of climate change. The results of DH estimation model show that location, access to credit, educational level and household size of the farmers are statistically significant factors influencing climate change perception (CCP). The result from the second hurdle shows that the perceived intensity of climate change was influenced by farm size, farming experience, marital status and educational level of smallholder rice farmers. The Ricardian model's result shows that farmers' income is influenced by CCP and their socio-economic characteristics. The results further indicate that smallholder rice farmers' net farm income is sensitive to marginal changes in both temperature and precipitation. Thus, this study recommends that government policies and investment strategies should be geared towards the support of education and the improvement of farmers' cooperatives, credit facilities and information about climate change, particularly in respect of smallholder rice farmers in Nigeria. The recommended improvements are imperative for food security. Investment in farmer training programmes is essential for development and may also be a panacea for improving the adoption of climate change adaptation strategies with the overall goal of increasing productivity.